2011
DOI: 10.1007/bf03253177
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of flonicamid and thiamethoxam on green peach aphid, Myzus persicae and feeding behavior analysis

Abstract: The green peach aphid, Myzus persicae Sülzer, is an important sap-sucking pest of many plants, including Chinese cabbage. The objective of the present study was to determine the effects of sublethal concentrations of two insecticides (flonicamid and thiamethoxam) and the action mechanisms on the feeding behavior of M. persicae. The median lethal concentrations (LC 50 ) of flonicamid and thiamethoxam for adult M. persicae were 2.56 and 4.02 mg/L, respectively. The sublethal concentrations of flonicamid were 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…If so, then A. biguttula may have preferred to lacerate and ingest from phloem, but may have switched their ingestion to mesophyll/parenchyma on flonicamid‐treated leaves to survive slightly longer than starved insects. Cho et al . found that flonicamid induced starvation in aphids with the inhibition of phloem sap ingestion, and that lower LC 50 values of flonicamid were associated with a decrease in the duration of phloem ingestion and increase in the Np period; these findings support the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…If so, then A. biguttula may have preferred to lacerate and ingest from phloem, but may have switched their ingestion to mesophyll/parenchyma on flonicamid‐treated leaves to survive slightly longer than starved insects. Cho et al . found that flonicamid induced starvation in aphids with the inhibition of phloem sap ingestion, and that lower LC 50 values of flonicamid were associated with a decrease in the duration of phloem ingestion and increase in the Np period; these findings support the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Sublethal concentrations (LC 30 ) of flonicamid and imidacloprid shortened the nymphal period of A. gossypii . In previous work, sublethal concentrations (LC 10 and LC 30 ) of flonicamid did not affect the nymphal period of the green peach aphid, Myzus persicae (Sulzer) (Cho et al., ). Boina et al.…”
Section: Discussionmentioning
confidence: 85%
“…However, feeding behavior was not inhibited by imidacloprid even at a concentration 2× higher than that recommended. The antifeedant effects of flonicamid lead to weight loss and subsequent death from starvation for M. persicae (Morita et al., ; Cho et al., ). Low concentrations of imidacloprid have been shown to have antifeedant effects (Nauen et al., ; Han et al., ), but it did not inhibit feeding behavior in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fecundity and reproduction after exposure to sublethal concentrations of insecticides have been reported (Morse 1998;Zanuncio et al 2003;Cutler et al 2009;Cho et al 2011). This may be one of the mechanisms of pest resurgence (Cutler et al 2009;James & Price 2002).…”
Section: Discussionmentioning
confidence: 94%